The marital announcements of persons of di erent church a liation - DÙLLEK, BOLESŁAW (Prawo Kanoniczne, 2017)
The origins of the marital announcements issue concerning persons of dierent church aliation, go back to the eighteenth century. Since then, this issue has been regulated by the particularistic law, which was largely conditioned by the civil law. So far, there has been formulated only one do- cument of general nature which focuses on this subject – Pio-Benedictine Code. Codication of John Paul II does not mention the discussed issue. In Poland the discussed issue appears in the Polish Episcopal Conference Instructions on preparing for marriage in the Catholic Church and in the Polish Episcopal Conference Instructions on the pastoral care for marriages of dierent church aliation. However, they do not give clear guidelines, but some tips which certain standards of conduct can be inferred from. Perhaps the new Polish Episcopal Conference Instruction on marriage in the Catholic Church, which is being presently prepared, will regulate this issue in detail.